Hubungan Pengetahuan Ibu Tentang Penerapan Pijatan Stimulus Touch Dengan Peningkatan Kualitas Tidur Pada Bayi - Afriza , Nurul; Syahadah, Nurul Fatehah; Azkiah, Novi; Zega, Ningsisari; Sondang, Mega; Paninsari, Debora (Journal of Pharmaceutical and Sciences, 2025)
Background: Baby massage is a non-pharmacological stimulation technique believed to improve infant sleep quality through gentle touch that stimulates the nervous system and circulation. A mother's knowledge of massage techniques plays a vital role in its effectiveness. Objective: To determine the relationship between maternal knowledge of stimulus touch massage application and the improvement of infant sleep quality at Siti Hajar Clinic. Methods: This study used an analytical survey design with a cross-sectional approach. A total of 30 mothers with infants aged 0–12 months who visited Siti Hajar Clinic in April 2025 were selected using total sampling. Data were collected using a questionnaire and analyzed using the Chi-Square test. Results: Based on the results obtained, out of the total respondents, the majority—27 mothers with good knowledge—had babies whose sleep quality improved, representing 90%. Two respondents with moderate knowledge also experienced improved sleep quality in their babies (6.7%), while one respondent with poor knowledge showed no improvement in the baby's sleep quality (0%). Statistical analysis revealed a significant result (p = 0.000 < 0.05), indicating a relationship between maternal knowledge and improved infant sleep quality. Conclusion: There is a significant relationship between maternal knowledge of stimulus touch massage and the improvement of infant sleep quality.